Minimum Quantity Lubrication (MQL) and its effect on tool wear during miniature drilling: an experimental study - Mohamad, Norsalawani; Bahar, Rubina (Deerhill Publishing, 2016)
Miniature drilling is widely used in industries including electronics and reconstructive surgeries to create small sized holes. Chip removal and effective supply of coolant are the two limiting factors that make the process more complex compared to other meso scale machining processes and also contribute to the tool wear. The tool wear in the process is mainly caused by the interaction, motion and chip production between the tool and work piece. Uniform supply of coolant must be ensured to reach the drilled cavity to keep the tool wear to a minimal level. This study includes experimental investigation of the tool condition after applying Minimum Quantity Lubrication (MQL) system as a greener approach as the name indicates. The tool condition with MQL has also been compared with dry and flood cooling. Two different types of drill bit materials (High Speed Steel and Carbide) have been tested under same experimental condition to drill through Aluminum Alloy 6061 and it has been found that overall performance in terms of tool condition after applying MQL was better compared to the other two methods. The overall wear propagation area was measured for both the conditions. It was seen, the wear propagation covered minimal area with MQL while for flood and dry condition wear was spread over a bigger area on flank.